THE PROBLEM OF SYNONYMY IN THE TERMINOLOGY OF INTERIOR DESIGN IN THE UZBEK LANGUAGE (The Conference Hub, 2025)
This article provides a linguistic analysis of the issue of synonymy in the Uzbek-language terminology of interior design. The study examines the presence of synonymous terms, their distinctions, and their role within the terminological system. While synonymy in interior design terminology contributes to terminological accuracy and clear communication, excessive synonymization may sometimes lead to misunderstandings. The article explores the specific features of lexical-semantic and technical synonymy, emphasizing the need for term standardization and the creation of specialized dictionaries. The research findings highlight the importance of systematically addressing synonymy issues to enhance the development of interior design terminology.